What (Business) Women Want - Employing Surveys to Expand Our Knowledge About the State of Female Entrepreneurship in MENA Region - Niethammer, Carmen; Gharbi, Hela (World Bank, Washington, DC, 2012)
Women's entrepreneurship is increasingly recognized as an important factor for economic growth and private sector development. Yet across the world, little quantitative information on female-owned businesses is available to inform policymakers how to better support them or to provide assistance to the rising number of women's business associations that are looking to better serve their membership base. In 2005, International Finance Corporation (IFC) commissioned four country assessments on the state of women's entrepreneurship in Middle East and North Africa (MENA). These assessments filled an important knowledge gap and drew attention from female entrepreneurs, businesswomen's associations, policymakers, donors, and the media alike. Subsequently, IFC was approached by businesswomen's associations from other MENA countries to conduct surveys there as well. The request posed a challenge, as financing female entrepreneurship surveys in all 19 countries covered by IFC Private Enterprise Partnership (PEP)-MENA would not only be financially challenging but also require tremendous monitoring and supervision efforts.